Objective-C for Absolute Beginners iPhone, iPad, and Mac Programming Made Easy - Bennett, Gary.; Fisher, Mitch; Lees, Brad.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
It seems as if everyone is writing applications for Apple$1 (Bs iPhone and iPad, but how do they all do it? It$1 (Bs best to learn Objective-C, the native language of both the iOS and Mac OS X, but where to begin? Right here, even if you$1 (Bve never programmed before! Objective-C for Absolute Beginners will teach you how to write software for your Mac, iPhone, or iPad using Objective-C, an elegant and powerful language with a rich set of developer tools. Using a hands-on approach, you$1 (Bll learn to think in programming terms, how to use Objective-C to build program logic, and how to write your own applications and apps. With over 50 collective years in software development and based on an approach pioneered at Carnegie Mellon University, the authors have developed a remarkably effective approach to learning Objective-C. Since the introduction of Apple$1 (Bs iPhone, the authors have taught hundreds of absolute beginners how to develop Mac, iPhone,and iPad apps, including many that became popular apps in the iTunes App Store.s
Becoming a Great iPhone/iPad or Mac Programmer -- Programming Basics -- It$1 (Bs All About the Data -- Making Decisions About...and Planning Program Flow -- Object Oriented Programming with Objective-C -- Introducing Objective-C and Xcode -- Objective-C Classes, Objects, and Methods -- Programming Basics in Objective-C -- Comparing Data -- Creating User Interfaces with Interface Builder -- Memory, Addresses, and Pointers -- Debugging Programs with Xcode -- Storing Information -- Protocols and Delegates.s
Keywords: Computer science; Computer Science; Programming Techniques